The effect of building form on cooling load in hot and humid climate - Wan Mohamed Rashdi, Wan Shahrizatul Suraya (2016)
High energy consumption correspondingly starts from an inefficient use of energy. The communities are increasingly concerned towards a better usage of energy for more comfortable life in future. Since past decades the standard of living has improved, people tend to expect a better comfort level which they consider the usage of air conditioning system is a must. The design of a building is required to provide comfort and efficient energy usage. The research objectives are to study the concept and influence of building form and geometry, investigate the cooling load in building space and to explore building form strategies in decreasing the cooling load. The research investigates the development and relationship of basic geometrical building form in lowering cooling load of a medium five-storey building. The manifestation of different thermal behaviour of each basic form was based on different volume, height and surface. The study manipulates the variables in three steps. The first step is the exploration and understanding of basic forms having the same height level, volume and different surface. The second step is investigating further on basic form by having different height levels but same overall volume. The final step explores the same volume, height level and surface area of the geometric forms. The study was conducted using computer simulation analysis program Autodesk Ecotect 2011. The outcome of the research reveals that compact shape and lower ratios of surface to volume result in lower cooling loads. The building with a different floor height but same overall volume shows the effect of lowering the cooling load. The increase number of floor zones will give lower cooling load. Experimentation of the basic forms reveals that an exposed surface area plays a huge role in lowering cooling load. Compact arrangement of spaces in a building also gives impact towards cooling load. The result of simulation model analysis shows the orientation aspect is less significant with 0.5 to 0.6 % difference towards lowering the cooling load compared to the exposed surface area of the form that shows 5 up to 19 % difference of cooling load from each geometry form. This research is significant in helping to accumulate the information regarding building form behaviour. Based on the result, the manipulation of exposed surface of the basic building form will reduce the cooling load.